Learning Management System Difficulties during the Learning Process in Higher Education - Jasiyah, Rabiyatul; Rumahlewang, Emma; Mundung, Bertha Ireni; Sairdama, Syusantie Sylfia; Saputra, Nanda (Universitas Pendidikan Ganesha, 2024)
The implementation of learning management system, lecturers must prepare the necessary materials and components. However, the fact is that there are 63% difficulties in compiling material in the learning management system. The research aims to analyze the impact of implementing learning using LMS in higher education and to find solutions to overcome obstacles and difficulties in implementing learning using a learning management system. The research method used is a survey by distributing instruments. Data collection techniques were by distributing instruments to 132 people consisting of lecturers and students who are directly involved in the learning process and conducting random interviews to ensure the correctness of the data from the survey. Analysis techniques using SPSS Version 25.0 by forming bar charts, line charts, and pie charts and interpreting them. As a result, the obstacles, difficulties, and impacts of using the learning management system during the learning process were found. The obstacles and difficulties lie in the preparation of materials, models, and assessment tools used which are not provided to students through the LMS. The material is not stated in the media used and is not given an assessment to students, so the impact is that students are unable to measure their abilities. In conclusion, every lecturer must prepare materials, models, and assessment instruments before using the learning management system in implementing course learning.